The Moderating Role of Underwriter Reputation in the Relationship Between Financial Performance and Underpricing Levels - Dewi, Made Rani Kusuma; Gayatri, Gayatri; Wirama, Dewa Gede (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p15, 2024)
The situation in which the price of the stock in the initial offering is lower than the price of the stock in the secondary market is known as underpricing. This phenomenon results in the funds or capital obtained by the company being suboptimal. However, in order to secure an initial return on their investment, investors in the primary market prefer to see underpricing occur. This research aims to examine whether the impact of profitability, financial leverage, and liquidity on the degree of underpricing can be mitigated by the reputation of the underwriter. The study focused on non-financial firms that went public between 2018 and 2023. A purposive sampling technique was used to select the sample, resulting in 294 companies. The data for this study were analyzed using moderated regression analysis techniques. The study shows that underpricing is negatively affected by profitability and liquidity, and that underwriter reputation acts as a pure moderator of the effect of financial leverage on underpricing. Keyword: Underpricing, Initial Public Offering, Profitability, Financial Leverage, Liquidity, Underwriter reputation